2020
DOI: 10.1177/0748730420965291
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Jetlag Resetting of Behavioral, Physiological, and Molecular Rhythms in Proestrous Female Mice

Abstract: A gradual adaptation to a shifted light-dark (LD) cycle is a key element of the circadian clock system and believed to be controlled by the central circadian pacemaker, the suprachiasmatic nucleus (SCN). Endocrine factors have a strong influence on the regulation of the circadian clock network and alter acute photic responses of the SCN clock. In females, endocrine function depends on the stage of the ovarian cycle. So far, however, little is known about the effect of the estrous cycle on behavioral and molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 121 publications
(134 reference statements)
1
4
1
Order By: Relevance
“…Although activity rhythms were disrupted by 8 h advance and delay phase shifts, daily vaginal smears indicated that with very few exceptions estrous cycles were not interrupted in either genotype (data not shown). In contrast to observations in mice ( Pilorz, et al, 2020 ), the latency to re-entrain was unaffected in either genotype by the day of the estrous cycle on which hamsters were subjected to 8 h advances or delays.…”
Section: Resultscontrasting
confidence: 98%
“…Although activity rhythms were disrupted by 8 h advance and delay phase shifts, daily vaginal smears indicated that with very few exceptions estrous cycles were not interrupted in either genotype (data not shown). In contrast to observations in mice ( Pilorz, et al, 2020 ), the latency to re-entrain was unaffected in either genotype by the day of the estrous cycle on which hamsters were subjected to 8 h advances or delays.…”
Section: Resultscontrasting
confidence: 98%
“…They suggest that E2, acting via ERβ in the SCN rich in ERs, enhances circuitry coupling and reveals an additional function of E2 in astrocytes, influencing rhythmicity within SCN neurons. These observations propose that estrogen-mediated coupling could fortify the SCN, rendering it more resilient against environmental alterations, as observed in our recent study (Pilorz, Kolms, & Oster, 2020) during elevated E2 levels in the estrus cycle.…”
Section: Discussionsupporting
confidence: 79%
“…Per2 m/m females undergo reproductive aging faster than males (Pilorz and Steinlechner, 2008), and we do not know how long-term DD affects estrous cycling.Given the impact of female reproductive hormones on circadian rhythms in general and Per2 in particular (Nakamura et al, 2005, 2008), processes associated with reproductive aging may contribute to the sex difference in arrhythmia identified here or in part mask the effect of loss of estrous cycling (Pilorz et al, 2020). Pilorz and Steinlechner (2008) identified reproductive senescence in female Per2 m/m mice as beginning sometime after 6 months of age, as 9- to 12-month-old Per2 m/m females had reduced fertility compared with WT controls.…”
Section: Discussionmentioning
confidence: 94%